تجديد النظام التعليمي نحو تحقيق رؤية و رسالة المعاهد الإسلامية في سولاويسي الجنوبية - Abdul Kadir; Ambo Asse; Amirah Amirah; Muhammad Ali Bakri; M. Ilham Muchtar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This study aims to find out: 1) the role of the education system at Ummul Mukminin 'Aisyiyah Islamic Boarding School; 2) efforts to realize the vision and mission of Ummul Mukminin 'Aisyiyah Islamic Boarding School; and supporting and inhibiting factors in the role of the Ummul Mukminin 'Aisyiyah Islamic Boarding School education system. This research is located at the Ummul Mukminin 'Aisyiyah Islamic Boarding School, South Sulawesi, using a qualitative descriptive method along with SWOT analysis. The collected data were selected and analyzed semantically and inductively, supported by the results of direct observation. The research results show: 1) The role of the education system must follow developments in the National Education System which includes aspects of institutional and curriculum management; 2) Efforts to realize the vision and mission of Islamic boarding schools through success alumni, outstanding leaders at the local and national levels, nurturing cadres of scholars through the Tahfidz Al-Quran and Kemuhammadiyahan programs; 3) The supporting factors for achieving the vision and mission of the pesantren are adequate facilities and infrastructure, professional human resources, good leadership, effective communication and cooperation. Inhibiting factors, including; the absence of Information Technology-based blueprints, competition between Islamic boarding schools, the lack of budget support from the government.